Evaluating drugged driving: Effects of exemplar pain and anxiety medications. (28th February 2018) - Brown, Timothy L.; Milavetz, Gary; Gaffney, Gary; Spurgin, Andrew
ABSTRACT: Objective : Distracted and drug-influenced driving presents a major risk for traffic safety morbidity and mortality. As part of an ongoing research program, we examined the effects of a commonly prescribed combination of medications for pain relief: alprazolam, a benzodiazepine, and a hydrocodone preparation, a combination opiate and acetaminophen, on a simulated driving protocol. Methods : Utilizing a within-subjects design, we recruited 8 healthy experienced drivers without major physical and psychological histories. Using a double-blind, placebo-controlled crossover design, we administered placebo, alprazolam alone, hydrocodone/acetaminophen, and the combination of the 2 drugs in a standardized simulated driving protocol. Measures of lateral and longitudinal control were collected and the data were reduced and statically analyzed. Results : The study observed clear detrimental effects of alprazolam on driving measures of lateral control and longitudinal control. Driving appeared to more aberrant at higher speeds and in rural scenarios. There were no statistical differences between hydrocodone and placebo. A measure of sedation showed that subjects rated alprazolam as more sedating than both hydrocodone and placebo. Conclusions : The findings suggest that impairing effects of this commonly prescribed combination of pharmacologic agents impact simulated driving performance. Negative changes in driving performance included measures of lateral and longitudinal control, although the deleterious effects on lateral control measures such as standard deviation of lane position (SDLP) were larger and more robust. Although the number of subjects was small, thus making it more difficult to draw conclusions on the narcotic effects, these results suggest that in this combination of central nervous system (CNS)-active drugs the benzodiazepine alprazolam accounted for the majority of impairing drug effects. The effect sizes associated with the hydrocodone preparation ranged from very small to medium. These results have potential implications for prescribing physicians and dispensing pharmacists, traffic safety experts, law enforcement officers, and patients themselves.